Structural Analysis Based Fault Detection and Isolation Applied for A Lithium-Ion Battery Pack. Issue 21 (2015) - Liu, Zhentong; He, Hongwen; Ahmed, Qadeer; Rizzoni, Giorgio
Abstract: Structural analysis is a powerful graphic tool for the pre-analysis on the fault detectability and isolability possibilities without the accurate knowledge of system parameters. It helps to find the redundancy part of the system model through analyzing the system structural model, in which subset of equations can be extracted to calculate the unknown variables in an order and then to check the consistency relations to generate sequential residuals. Health operation of the battery management system for a lithium-ion battery pack heavily relies on the employed current, voltage and temperature sensors. This paper presents a systematic scheme to apply the structural analysis theory for a lithium-ion battery pack to detect and isolate the current sensor, voltage sensors and temperature sensor as well as cooling system faults. The simulation results confirmed the effectiveness of the proposed fault diagnosis scheme to handle the nonlinear dynamics efficiently, and to detect and isolate the considered faults.